"Mino-Bimaadiziwin in Atwood's Speculative Fiction." - Skibo-Birney, Bryn (2018)
This project follows the path blazed by such scholars as Jodi Byrd (Chickasaw Nation of Oklahoma), Glen Coulthard (Yellowknives Dene First Nation), Vine Deloria Jr. (Oglala Sioux), Lawrence Gross (White Earth Chippewa), Kwes Kwentin (Musqueam), Audra Simpson (Mohawk), Inés Talamantez (Mescalero Apache), and Zoe Todd (Red River Métis/Otipemisiwak), who have all argued for the value in using Indigenous epistemologies as critical theories in a largely non-Indigenous academic context. Following their research and their practice, my project uses the Anishinaabe epistemology of Mino-Bimaadiziwin, or “the good life,” to read Margaret Atwood's speculative “ustopian” (dystopia / utopia) novel, MaddAddam. While scholars have approached the novel, as well as the trilogy as a whole, in terms of post-structuralism, post-colonialism, post-humanism, feminism, and trauma narratives, few (if any) have addressed the novel in terms of Indigenous ways of seeing and being part of an interconnected and interdependent world. Some readers may question the relevance of Indigenous studies in this novel due, perhaps, to the near-absence of non-white characters in the trilogy; others may question the relevance of Margaret Atwood to the conversation of Indigenous studies in light of the criticisms brought against her fiction and non-fiction for their (stereotypical or appropriative) representation (or lack thereof) of Indigenous people and cultures and due to her participation in debates regarding the supposed claims of Native identity made by Canadian authors. Nevertheless, this paper argues that reading MaddAddam in terms of Mino-Bimaadiziwin highlights the epistemological significance of the novel's inventive use of discontinuous narrative, polyphony, and ambiguous endings, as well as the non-anthropomorphic use of non-human voices and discourse, both of which are illustrative of the novel's determined turn towards a non-anthropocentric and non-speciesist post-apocalyptic society. While these points share commonalities with the theories ...